The Recent Experience with Capital Flows to Emerging Market Economies - Blöndal, Sveinbjörn (OECD Publishing, 1999)
This paper summarises key points of the recent extensive discussion of the factors behind the volatility of cross-border capital flows in emerging market countries and possible corrective measures. The root cause of the recent volatility of capital flows seems to have been excessive credit and currency risk-taking by banks, which in turn was related to moral hazard problems, failure of prudential regulations and bank supervision, and weak effective standards of financial disclosure. Macroeconomic factors also played a role, with a widening deficit on the balance of payments and fixed (or predictable) exchange rates gradually undermining confidence of creditors and investors. Liquidity problems may have amplified the reaction to adverse news, and herd behaviour and contagion may also have exaggerated reaction to changing fundamentals and transmitted crises from one country to another. Capital controls, which have been extensively used in emerging market countries, may not be very ...
Keywords: Economics